Modern electronic communication - Miller, Gary M. 1941- (Prentice Hall, 1999)
This work features an accompanying Electronic Workbench CD to enable computer analysis of about 100 circuits in the text. It adds chapter-end questions and problems for all trouble-shooting sections, and includes a full trouble-shooting section at the end of each chapter.